Measurement of middle ear volume in adults using three-dimensional (3D) reconstruction multi-detector computer tomography (MDCT) scan - Rahman, Siti Khairunnisaak Abdul Rahman (2018)
Background: Computed tomography (CT) has emerged as a method of estimation of middle ear volume (MEV). The purpose of this study is to determine middle ear volume of adults using Three- Dimensional (3D) reconstruction Multi-Detector Computed Tomography (MDCT) in different age and gender. Methods: A total of 140 adult CT brain images were retrieved from Picture Archive Communication System (PACS). The CT brains were performed on Siemens SOMATOM Definition AS+ CT machine with a slice thickness of 1mm and high kernel bone algorithm. Images with complete mastoid air cells were included. Only good quality images were analysed. Images with abnormality of the skull, brain or ear were excluded. Ear Review of 3D application (GE PACS Universal Viewer Version 5.0 SP6) was used to measure the MEV. Results: The mean of right MEV was3.845cm3 (SD: 1.833) and left MEV was 3.855cm3 (SD: 1.843). The difference between the right and left MEV means are statistically not significant with p = 0.460, (95% CI: -0.035 to 0.016). No difference in mean MEV between male and female with p = 0.889, (95% CI: -0.658 to 0.571) and p = 0.934, (95% CI: -0.644 to 0.592) for right and left MEV respectively. Weak negative correlation with age was shown with r = -0.101, p = 0.233 for right MEV and r = - 0.102, p = 0.232 for left MEV respectively. Conclusion: This study can contribute to provide baseline data for further studies on mastoid pneumatisation. MEV measurement using 3D reconstructed MDCT is easily available and reproducible